Low-frequency noise measurements at liquid helium temperature operation in ultra-thin buried oxide transistors – Physical interpretation of transport phenomena. (December 2018) - Nafaa, B.; Cretu, B.; Ismail, N.; Touayar, O.; Carin, R.; Simoen, E.; Veloso, A.
Highlights: FD SOI UTBOX devices have been studied at helium liquid temperature. Transfer characteristics at very low temperature and polarization evidenced step-like effect that can be associated to energy band scattering. The change of the dominant carrier transport mechanism (drift-diffusion versus quantum) is accompanied by a change of 1/f fluctuations mechanism (carrier number versus mobility fluctuation mechanisms). Abstract: In this work, UTBOX SOI nMOSFETs have been studied at liquid helium temperature (i.e. 4.2 K). Transfer characteristics at very low temperature and polarization evidenced step-like effects that can be associated to energy subband scattering. Low frequency noise measurements were performed at the same temperature in polarization conditions corresponding to drift-diffusion and quantum transport related to energy subband scattering, respectively. A theoretical approach valid in moderate inversion is constructed for the mobility fluctuations and carrier number fluctuations with correlated mobility fluctuations models at this temperature operation. It was observed that flicker noise originates from carrier number fluctuations when the drift-diffusion transport is dominant. In quantum transport related to energy band scattering condition, the results suggest that the mobility fluctuations mechanism is suitable to explain the flicker noise behavior.